Simulation of Tied-Arch Bridge Design on Ibu Kota Nusantara (IKN) - Hermawan, Rahmat; Pamadi, Mulia (Journal of Infrastructure and Civil Engineering, 2025)
The relocation of Indonesia's capital to Ibu Kota Nusantara (IKN) in East Kalimantan necessitates the development of robust infrastructure, particularly bridges. This research focuses on the design simulation of a tied-arch bridge for IKN, addressing challenges such as limited skilled human resources, budget constraints, and environmental considerations. The primary objective is to create a simulation model that integrates structural durability, ecological sustainability, and aesthetics. The bridge's design was meticulously modeled and analyzed using SAP2000 software under various load conditions to ensure strength and stability. The methodology involved collecting technical and environmental data, simulating the bridge model, and evaluating its feasibility. The results indicate that the proposed tied-arch bridge design can effectively withstand dynamic and static loads, ensuring safety and functionality. The study concludes that integrating civil engineering disciplines in bridge design is crucial for achieving efficient, durable, and aesthetically pleasing structures. The simulation model provides practical guidance for stakeholders involved in the planning and constructing of bridge infrastructure in IKN, contributing significantly to the knowledge base in this field and supporting the vision of IKN as a sustainable and iconic capital city